Lombalgia equina: diagnóstico e tratamento - Mendes, Adriana Borges; Figueiró, Giuliano Moraes; Lucas, Flávia de Almeida [UNESP]; Barioni, Graziela (My University, 2013)
Low back pain is considered a major cause of lameness and performance decay, but identify the location of the lesions and quantify the intensity of pain is difficult because often the most obvious clinical sign, in some cases, is not the pain itself, but, low athletic performance. The diagnosis and treatment of this disease are associated with a high cost and have a strong impact on the equine industry, since it results in direct economic losses. The diagnosis of low back pain is made through physical examination and additional tests, including radiography, ultrasound, thermography and blockades. Major injuries causing back pain in horses is the contact or overlap of the spinous processes, supraspinous desmitis, osteoarthritis of the articular processes, vertebral body lesions and myositis. Therapeutic measures used in the treatment of these diseases are systemic inflammatory steroid, local infiltration, acupuncture, chiropractic, physical therapy, changes in training and surgeries.

A lombalgia é considerada uma causa importante de claudicação e queda de performance, porém identificar a localização das lesões e quantificar a intensidade da dor é difícil, pois frequentemente o sinal clínico mais evidente, em alguns casos, não é a dor propriamente dita e sim, o baixo desempenho atlético. O diagnóstico e tratamento desta enfermidade estão associados a um alto custo e possuem um forte impacto na indústria equina, uma vez que resulta em perdas econômicas diretas. O diagnóstico das lombalgias se faz por meio do exame físico e dos exames complementares, que incluem radiografia, ultra-sonografia, termografia e bloqueios anestésicos. As principais lesões causadoras de lombalgias nos equinos são o contato ou sobreposição dos processos espinhosos, a desmite supraespinhosa, a osteoartrite dos processos articulares, as lesões de corpo vertebral e a miosite. As medidas terapêuticas utilizadas no tratamento destas enfermidades são antiinflamatórios esteróides sistêmicos, infiltrações locais, acupuntura, quiropraxia, fisioterapia, modificações no treinamento e cirurgias.
Equine back pain: diagnosis and treatment
Keywords: Horses; Back pain; Lameness; "Kissing spines"; Desmitis; Osteoarthritis; Spinal spondylosis; Equinos; Lombalgia; Claudicação; “Kissing spines”; Desmite; Osteoartrite; Espondilose vertebral